2018
DOI: 10.2147/oarrr.s130176
|View full text |Cite
|
Sign up to set email alerts
|

<div>Serum IL-6 correlates with axial mobility index (Bath Ankylosing Spondylitis Metrology Index) in Brazilian patients with ankylosing spondylitis</div>

Abstract: IntroductionAnkylosing spondylitis (AS) is a chronic disease featuring axial changes, peripheral arthritis and systemic involvement. Proinflammatory cytokines are probably involved in AS pathogenesis. The relationship of circulating cytokines with instruments of AS evaluation is an open field of research.ObjectiveThe aim of this study was to compare serum levels of cytokines in AS patients and healthy controls, and search for correlations of cytokines with indexes of disease activity and quality of life.Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…AS is a type of rheumatism characterized by chronic inflammation of the axial joint and may involve the internal organs and other tissues [33]. TNF-α, IL-6, IL-8, and IL-17 have been identified to be overexpressed in AS patients [34]. Furthermore, in AS patients, neutrophils are activated so that reactive oxygen species are generated, resulting in oxidative stress [35].…”
Section: Discussionmentioning
confidence: 99%
“…AS is a type of rheumatism characterized by chronic inflammation of the axial joint and may involve the internal organs and other tissues [33]. TNF-α, IL-6, IL-8, and IL-17 have been identified to be overexpressed in AS patients [34]. Furthermore, in AS patients, neutrophils are activated so that reactive oxygen species are generated, resulting in oxidative stress [35].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, TNF- α , a classic proinflammatory factor, can mediate an inflammatory cascade and promote the upregulation of various inflammatory factors, such as IL-6, IL-1 β , and IL-8 [ 35 ]. It also can directly stimulate inflammatory cells and catalyze inflammatory reactions to induce tissue cell damage [ 36 , 37 ], which is closely related to the pathological changes in AS. Clinically, biologics targeting TNF- α are important drugs used in western medicine for the treatment of AS.…”
Section: Discussionmentioning
confidence: 99%
“…In a 5‐year prospective study of 166 patients with axial SpA in Sweden, a high BASMI score predicted radiographic progression, although only in women (44). In a recent meta‐analysis examining factors associated with high interleukin‐23 (IL‐23) levels in patients with axial SpA, including 10 studies with 1,724 patients, the BASMI score was 1 of 2 factors, along with inflammatory markers (ESR and CRP level), to be positively associated (correlation coefficient 0.46 [95% CI 0.03, 0.75]) (45), while a small study of 32 patients with AS in Brazil demonstrated a significant correlation with IL‐6 (46). Mewes et al (2019), in a small study of 55 patients with axial SpA, showed a strong association between a high BASMI score and poor balance, which in turn was linked to a higher risk of falls (47).…”
Section: Discussionmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved correlation with IL-6 (46). Mewes et al (2019) in a small study of 55 patients with axSpA showed a strong association between a high BASMI score and poor balance, which in turn was linked to a higher risk of falls (47).…”
Section: Accepted Articlementioning
confidence: 97%